PENERAPAN MEDIA ‘PUPUH GINADA (SEKAR ALIT)’ UNTUK MENINGKATKAN KEMAMPUAN MENULIS CERPEN YANG BERORIENTASI NILAI KARAKTER PADA SISWA KELAS VII A SMP NEGERI 1 TEJAKULA - Kurniawan, Kadek Ferri (Universitas Pendidikan Ganesha, 2013)
ABSTRACT This research is a qualitative and quantitative descriptive research that aims to find the skills to write short stories A class VII student at SMP Negeri 1 Tejakula, when taught using media pupuh ginada (sekar alit). The sample was all class VII A in SMP Negeri 1 Tejakula Academic Year 2012/2013. The number of students sampled was 38 and an Indonesian teacher in class VII A. Data collection in the study used media observation, questionnaires, and tests. The data obtained from the observations were analyzed with descriptive qualitative techniques, while the data obtained from the questionnaires and tests using quantitative descriptive technique. The results of this study were (1) Application of media pupuh ginada (sekar alit) can improve students' ability to write short stories. (2) The title of the short story by the example of the teacher allows students to make the title short story. (3) Providing guidance and recognition by teachers can encourage students to be better. (4) The response of the students affect the behavior of students in participating in learning to write short stories using media stanzas ginada (sekar alit).